PENGARUH ANALISIS STRATEGI DIGITAL MARKETING DAN KEPERCAYAAN MEREK DALAM MEMBENTUK KEPUTUSAN PEMBELIAN: STUDI KASUS DI TOKO RODEO RAJANYA KANDANG - Aldio Farri Reza; Defrizal (CV. Lafadz Jaya, 2026)
This study aimed to analyze the influence of digital marketing strategies and brand trust on purchasing decisions at the Rodeo Rajanya Kandang store. This research employed a quantitative approach, utilizing SPSS software as a data analysis tool. To assess data quality, validity and reliability tests were conducted, followed by a series of classical assumption tests: normality, multicollinearity, and heteroscedasticity. Hypothesis testing was conducted using a t-test, followed by a coefficient of determination analysis. This study involved 100 respondents, with the entire population being sampled using a saturated sampling technique. Data processing revealed that digital marketing strategies and brand trust have a positive and significant influence on purchasing decisions at the Rodeo Rajanya Kandang store.